The classroom management-based teams games tournament (tgt) learning model in improving civics education learning outcomes - Purnamasari, Sonya; Sanoto, Herry (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
Civics Education (PPKn) in elementary schools is often perceived as less engaging due to its conceptual nature and conventional teaching methods, leading to low student learning outcomes. This study aims to examine the effect of the Teams Games Tournament (TGT) model integrated with classroom management on fourth-grade students' Civics learning outcomes. A quasi-experimental method was used with a Posttest Only Non-Equivalent Control Group Design. The subjects were two fourth-grade classes, each consisting of 29 students. The experimental group was taught using the TGT model, while the control group received traditional instruction. A multiple-choice test with 25 validated items was used to measure learning outcomes. Data analysis involved normality and homogeneity tests, followed by an Independent Sample T-Test. The findings showed a significant difference between the two groups (sig. 0.011 < 0.05), with the experimental group scoring higher on average. These results indicate that the TGT model supported by effective classroom management can improve Civics learning outcomes. Therefore, this model is recommended as an engaging and effective alternative to conventional methods in Civics Education.